The usage of interactive methods for the formation of foreign language communicative competence of primary school students - Assylzhanova, Danagul; Sadykova, A.K. (Pedagogy and Psychology, 2024)
The article deals with the problem of formation of foreign language communicative competence of primary school students during English language teaching. In modern conditions, changes in the demands of society occur rapidly, the importance of communicative competence increases already in the conditions of primary school education. There is a need to use new forms of education in the process of education. Due to the fact that the skills of interpersonal communication are not sufficiently developed at a young school age, many obstacles arise, due to which the child can become withdrawn, not succeed in the program, or create difficulties for the teacher in the process of teaching the material. The author uses communicative exercises and game tasks, as well as information and communication technologies, interactive electronic books, which can be effectively applied both in the classroom and in extracurricular activities, as the main didactic tools for the formation of the communicative competence of younger schoolchildren. The analysis of the results of the experiment allowed us to conclude that the majority of young learners have developed foreign language communicative competence and communication skills, the ability to coordinate efforts in the process of organizing and implementing cooperation.